2020
DOI: 10.1039/d0ra01444c
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of lignin-based colloidal particles: effects of cationic surfactants, molecular weight, and solvent on morphology

Abstract: Effect of cationic surfactants, molecular weight and solvent on the morphology of lignin based particles and in vitro release behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is clearly shown that KL-NPs had excess amorphous or small particles surrounding the surfaces due to the mixed Route C and D. AKL-NPs are mainly local clusters, representing Route C. The morphology of AKL-NPs is similar to the reported cationic LNP when 1,4-dioxane was the solvent and DI water was antisolvent. 58 For the EKL that mainly has low molecular weight fractions, the morphology looks similar to KL-NPs at the lower concentration and suggests the LNP formation follows Route E. The difference reflects the self-assembly patterns between large and small molecular weight fractions. While it brings a more negatively charged surface to the aggregated particles, non-DLVO forces get involved (Route F).…”
Section: Resultsmentioning
confidence: 93%
“…It is clearly shown that KL-NPs had excess amorphous or small particles surrounding the surfaces due to the mixed Route C and D. AKL-NPs are mainly local clusters, representing Route C. The morphology of AKL-NPs is similar to the reported cationic LNP when 1,4-dioxane was the solvent and DI water was antisolvent. 58 For the EKL that mainly has low molecular weight fractions, the morphology looks similar to KL-NPs at the lower concentration and suggests the LNP formation follows Route E. The difference reflects the self-assembly patterns between large and small molecular weight fractions. While it brings a more negatively charged surface to the aggregated particles, non-DLVO forces get involved (Route F).…”
Section: Resultsmentioning
confidence: 93%
“…However, the increase in the oil removal efficiency did not change significantly with the continuous increase in pH. The surface tension remained unchanged, resulting in a stable oil removal efficiency of OS [ 33 ]. Therefore, the optimum pH was determined to be 13.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that the cellulose, lignin and their derivatives are good candidates to prepare the effective flocculants. However, most flocculants prepared have the disadvantages of high flocculant dose, narrow pH window, complex chemical modification process and additional high cost from the chemicals used (Aro et al 2017;Chen et al 2020;Dutt et al 2020;Liu et al 2020;Oveissi et al 2016;Yang et al 2017).…”
Section: Introductionmentioning
confidence: 99%